1993
DOI: 10.1128/mcb.13.1.449
|View full text |Cite
|
Sign up to set email alerts
|

Two alleles of a developmentally regulated alpha-tubulin locus in Physarum polycephalum replicate on different schedules.

Abstract: The replication timing of a pair of natural alleles was compared at two ac-tubulin loci of the Physarum plasmodium. Taking advantage of the naturally synchronous cell cycle of nuclei within the syncytial plasmodium, we analyzed the replication schedule of specific DNA fragments to a resolution of 10-min intervals within a 3-h S phase. At this level of resolution, differences in replication timing between polymorphic alleles at the same locus can be detected in a heterozygote. Specifically, the 3' region of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Altogether, these results suggest a delayed activation of the origin in a small part of the nuclei contained within a plasmodium or they reflect different replication patterns of the two alleles contained within each nucleus. Although our previous studies have clearly shown a concerted activation of allelic origins at other loci ( 28 , 32 ), such a different replication pattern between two alleles has been already described in Physarum ( 47 ). From a gene dosage analysis, the authors found that the 2 allelic alt B1 and alt B2 alpha-tubulin loci replicate synchronously in early S phase, while alt A locus replicates later.…”
Section: Discussionmentioning
confidence: 49%
“…Altogether, these results suggest a delayed activation of the origin in a small part of the nuclei contained within a plasmodium or they reflect different replication patterns of the two alleles contained within each nucleus. Although our previous studies have clearly shown a concerted activation of allelic origins at other loci ( 28 , 32 ), such a different replication pattern between two alleles has been already described in Physarum ( 47 ). From a gene dosage analysis, the authors found that the 2 allelic alt B1 and alt B2 alpha-tubulin loci replicate synchronously in early S phase, while alt A locus replicates later.…”
Section: Discussionmentioning
confidence: 49%
“…Interestingly, the checkpoint-constrained replication origins locate to telomeric heterochromatin regions that are enriched in histone H3K9 methylation [Correction made here after initial online publication]. A relaxation of replication timing control in late replicating heterochromatin in Physarum polycephalum (C-value 0.3 pg) has also been suggested (Cunningham and Dove 1993;Diller and Sauer 1993;Bénard et al 1996), which would be consistent with a weaker inhibition of late-firing replication origins in organisms with small genomes.…”
Section: Genome Size Checkpoint Proficiency and Mutation Rate Hetermentioning
confidence: 81%
“…In G 2 phase, all three genes are replicated, providing a standard for normalizing hybridization values in a DNA sample containing two copies of each gene (2/2/2). At one time point in S phase, if one gene replicates earlier than the others, the relative copy number is changed (1/2/1) and the abundance ratio of the hybridization signals varies (31,35). Using this principle, we determined that redB replicates in the interval 0-30 min of S phase, like the early-replicating proP gene, whereas redA replicates mainly during the 60-90 min interval (Fig.…”
Section: Timing Of Replication Of the Red Genesmentioning
confidence: 99%
“…It has been previously shown by gene dosage experiments that within the same plasmodium, one allele of the weakly expressed α-tubulin altA gene completed replication in a large interval between 40 and 80 min in S phase, when the other allele was found to replicate earlier and more rapidly between 20 and 40 min in S phase (35). It was hypothesized that the more relaxed time schedule of replication of one of these alleles might result from a long distance between the gene and its replication origin and a random variation in the fork rate movement along the template.…”
Section: The Reda Promoter Region Coincides With An Origin Of Dna Repmentioning
confidence: 99%